Reading Effectively Across the Disciplines (READ): A Strategy to Improve Student Success - Juanita C. But; Pamela Brown; Davida S. Smyth (Park University, 2017)
This paper describes the structure and activities of READ (Reading Effectively Across the Disciplines), a pilot initiative to improve students' critical reading skills, disciplinary literacy and academic success. READ employs a multimodal design that consists of faculty training in disciplinary literacy instruction and curricular enhancement, development and implementation of active reading assignments and assessments, peer-led team learning, and the dissemination of discipline-specific teaching and learning resources on an Open Lab site to provide an interactive teaching and learning environment for students and faculty. Empirical evidence of the initial effectiveness of the pilot in three gateway courses in Biology, Electromechanical Engineering Technology, and Marketing showed improvement in student pass rates after implementation of reading strategies and instructional approaches that guide students through the reading process.